(untitled) (Research, Society and Development, 2021)
The purpose of this article was to present, through a literature review, the effectiveness, safety and satisfaction of patients with the use of calcium hydroxyapatite as a filler and as a collagen biostimulator. This is a literature review carried out through an active search for scientific articles in the database: U.S. National Library of Medicine (PubMed), using the search term: calcium hydroxylapatite cosmetic. Sixty nine publications were selected, from 2016 to 2021, however, based on the inclusion and exclusion criteria, 20 articles were selected. Based on the literature review carried out in this study, calcium hydroxyapatite was effective as a biostimulator of collagen and elastin; as a filler it presented a better lift effect (except in the case of eyebrow lift) because of its high modulus of elasticity, which can be used as a support for other fillers and support threads; had a high level of patient satisfaction; it is considered a material with a good safety profile, as long as the technique and indications are respected; and can be viewed on radiographs, tomographies and high resolution ultrasounds.